Women's right versus rights of women: A textual glance through the qur'anic mirror - Mohammed Muneer'deen, Olodo Al-Shafi'i; Mohd Safri, Ali; Engku Ibrahim, Engku Wok Zin; Razali, Musa (2018)
Discussions concerning women and rights are always ever-green debates that have attracted the global attention, from intellectual to the novice, religion and non-religion. It has gained so much popularity, so much so that there are several organizations, governmental and non-governmental, claiming to champion the cause from various facets of life. The religious authorities have also not failed in treating and addressing the pros and cons of issues related to women and rights, and, in some other times, gender equality related causes. While the religiously engaged intellectuals are treating women and rights through the religious textual mirrors, the so-called champions of women’s right are approaching same through the purely conventional background. Islam as a religion has an already stipulated guides to all-in-all of this, through the glorious book, al-Qur’an. This paper is aimed at clarifying the conception and misconception between the two phrases ‘Women’s right’ and ‘Rights of Women’ from the perspective of the Qur’an. The paper projects that the two phrases look similar in conception, but are distinct in context, because it is one thing to ‘have rights’ and quite another to ‘claim rights’. Do women have rights naturally stipulated to them or not? If affirmed, why fighting over what is naturally already theirs, and if it is in negation, why claiming what they are not destined to? The main method the paper employs here is basically textual analysis and elaboration of verses related to women and rights, as well as the review of previous scholastic writings found related. The paper posits that for women to enjoy their full empowerment there has to be detailed and comprehensive understanding of what is ‘women’s right’ and the ‘rights of women’. If this is done, the whole issue could be laid to rest.